Blueprint for revolution : how to use rice pudding, lego men, and other non-violent techniques to galvanise communities, overthrow dictators, or simply change the world /: how to use rice pudding, lego men, and other non-violent techniques to galvanise communities, overthrow dictators, or simply change the world. (2015) - Popovic, Srdja; Miller, Matthew
No abstract available